The cycle of violence? An empirical analysis of fatalities in the Palestinian-Israeli conflict - David A. Jaeger; Marco Daniele Paserman (Institute for the Study of Labor (IZA), 2005)
This paper studies the dynamics of violence in the Palestinian-Israeli conflict since the outbreak of the Second (or Al-Aqsa) Intifada in September 2000, during which more than 3,300 Palestinians and more than 1,000 Israelis have been killed. The conflict has followed an uneven pattern, with periods of high levels of violence and periods of relative calm. Using data on the number of deaths occurring each day between September 2000 and January 2005, we estimate reaction functions for both Israelis and Palestinians and find evidence of unidirectional Granger causality from Palestinian violence to Israeli violence, but not vice versa. This finding is consistent whether we look only at the incidence of fatalities or whether we look at the level of fatalities, and is robust to the specification of the lag structure and the level of time aggregation. We find little evidence that violence on either side has a direct deterrent or incapacitation effect. We do find, however, that successful assassination attempts do reduce the number of subsequent Israeli fatalities. We conclude that, despite the popular perception that Palestinians and Israelis are engaged in tit-for-tat violence, there is no evidence to support that notion.
Keywords: C32; D71; D74; H56; 330; Intifada; terrorism; Granger causality; Politische Gewalt; Kausalanalyse; Schätzung; Palästina; Israel